Sexpert Seksuele gezondheid in Vlaanderen - Buysse, Ann (Academia Press, 2013)
Sexual health in Flanders describes the results of the first representative population-based study on this topic in Flanders (the Northern, Dutch-speaking part of Belgium). A research team of psychologists, sexologists, sociologists and medical doctors, affiliated with Ghent University, KU Leuven and Ghent University Hospital collaborated on this research project that aimed to explore various aspects of sexual behavior and sexual health in men and women living in Flanders. Apart from providing in reliable, valid, descriptive scientific data, this study offers important information on which a more targeted policy to promote sexual health can be developed. This reference work is based on a survey in which 1832 Flemish men and women - aged 14 to 80 years old - participated and that covered various aspects of sexual health. The focus is not only on sexual experiences and practices; attention is also paid to the relational and social context in which these experiences occur. In addition, a number of chapters elaborate on the sexual start (the first sexual experiences), reproductive health, sexual dysfunctions, cross-border sexual behavior, and profiles of sexual health. The detailed description of the methodology that was used, allows the reader to evaluate the accuracy of the many tables, figures and numbers that are presented. In short, Sexual health in Flanders is an essential reference work for anyone with an interest in a reliable, detailed and scientific image of a broad range of aspects of sexual health in Flanders.